Colour Doppler study of extra cranial carotid vessels in South Indian population - Kumari, T. Muni; SadhanaBonda, P. N. R. (International Journal of Research in Medical Sciences, 2017)
Background: Colour doppler is non-invasive, cheaper and faster modality for evaluation of extra cranial course of carotid vessels. In evaluation of the extra cranial territory and its accuracy colour Doppler sonography was well established in comparison with angiography. Aim was to study the extra cranial carotid vessels by using colour doppler sonography. Methods: A total of 80 patients were examined by duplex sonography who were attending the medical department of Osmania medical college and hospital, Hyderabad, Telangana, India, from June 2014 to December 2015. Results: Highest incidence of the carotid disease is in the age group of 30 to 60 years. Out of 21 positive patients 13 patients were males and 9 were females. Male to female ratio is 1.5:1. Spectral trace was obtained in all the patients and cardinal four velocity parameters were measured. Takayasu’s arteritis is found to be more common carotid disease second to atherosclerosis in present study. Conclusions: Principal cause of carotid disease in Present study is atherosclerotic plaques. Atherosclerotic plaques are mostly found at the level of carotid bifurcation and the internal carotid artery. We suggest that colour doppler is significant advancement in carotid diagnosis.